The distribution and host selection of the chigger mite Leptotrombidium yongshengense (Acari: Trombiculidae) in southwest China - Chen-Xi Liu; Xian-Guo Guo; Yan Lv; Peng-Wu Yin (Persian Journal of Acarology, 2025)
Chiggers are the exclusive vector of scrub typhus, and Leptotrombidium yongshengense (Acari: Trombiculidae)is one of over 3,000 chigger species recorded. This paper reports the distribution and host selection of L. yongshengense in Southwest China for the first time. Leptotrombidium yongshengense was abundant in outdoor habitats in mountainous areas with middle and high altitudes. Most L. yongshengense were identified from adult hosts and showed an obvious host preference for Alexandromys oeconomus. Leptotrombidium yongshengense was found to have an aggregated distribution among different individuals of its hosts.